Faktor-Faktor yang Mempengaruhi Niat Mahasiswa Pendidikan Ekonomi untuk Menggunakan ChatGPT dalam Pembelajaran: Penerapan Model UTAUT - Aprillani Muntya Sari; Eka Hendi Andriansyah (Yayasan Al-Afif, 2026)
Technological developments in the world of education are increasingly developing, one of which is the emergence of generative AI such as ChatGPT, which has been widely used to assist in academic activities. However, the accuracy of the information generated by ChatGPT is sometimes misleading, which can affect students' intentions to use ChatGPT. This study aims to analyze the factors that influence the intention to use ChatGPT by economics education students in East Java using the UTAUT model. A quantitative approach with a survey method in the form of a questionnaire was used in this study. The population used in this study included all undergraduate economics education students in East Java who have used ChatGPT in learning. The sampling technique in this study used simple random sampling and the number of samples used in this study was 170 respondents. Online questionnaires were distributed via Google Forms to collect data in this study, and PLS-SEM with the help of SmartPLS 4 software was used for research data analysis techniques. This study found that all variables in the UTAUT model, including effort expectancy, facilitating condition, performance expectancy, and social influence, have a positive effect on students' intentions to use ChatGPT. This shows that the intention to use ChatGPT among economics students is influenced by perceptions regarding ease of use, availability of supporting facilities, performance benefits, and social support.